The EFFECT OF REWARD, PUNISHMENT AND WORK DISCIPLINE ON THE PERFORMANCE OF LECTURERS OF PANCASETIA ECONOMIC SCIENCE HIGH SCHOOL OF BANJARMASIN - Abdul Kadir; Fredy Jayen (Archives of Business Research, 2021)
This study aims to analyze the effect of reward, punishment, and work discipline on the performance of lecturers at the Pancasetia School of Economics Banjarmasin. The research method used is a questionnaire distributed to 40 lecturers at the Pancasetia School of Economics Banjarmasin as respondents. The measurement uses a Likert scale with a weight scale of 1 to 5. The results showed that reward had a positive effect on lecturer performance, the punishment had no positive effect on lecturer performance and work discipline had a positive effect on lecturer performance at the Pancasetia School of Economics Banjarmasin. Based on the Coefficient of Determination Test, the effect of the variable reward, punishment, and work discipline simultaneously on the performance of educators and education personnel is 0.630 while the remaining 37% is influenced by other variables not examined in this study. This figure means that the effect of reward, punishment and work discipline together is closely related to the performance of educators and education staff.